The Santa Filomena meteorite shower: Trajectory, classification, and opaque phases as indicators of metamorphic conditions - Tosi, Amanda; Zucolotto, Maria Elizabeth; Andrade, Diana Paula; Winter, Othon Cabo [UNESP]; Mourão, Daniela Cardozo [UNESP]; Sfair, Rafael [UNESP]; Ziegler, Karen; Perez, Pablo Daniel; Suarez, Sergio; Ornellas, Iara Deniz; Zurita, Marcelo; Mendes, Julio Cezar; et al. (Wiley, 2023)
On August 19, 2020, at 13:18—UTC, a meteor event ended as a meteorite shower in Santa Filomena, a city in the Pernambuco State, northeast Brazil. The heliocentric orbital parameters resulting from images by cameras of the weather broadcasting system were semimajor axis a = 2.1 ± 0.1 au, eccentricity e = 0.55 ± 0.03, and inclination i = 0.15o ± 0.05. The data identified the body as an Apollo object, an Earth-crossing object with a pericenter interior to the Earth's orbit. The chemical, mineralogical, and petrological evaluations, as well as the physical analysis, followed several traditional techniques. The meteorite was identified as a H5-6 S4 W0 ordinary chondrite genomict breccia. The large amount of metal in the meteorite made a metallographic evaluation based on the opaque phases possible. The monocrystalline kamacite crystals suggest a higher petrological type and the distorted Neumann lines imply at least two different shock events. The absence of the plessite phase shows that the meteorite did not reach the highest shock levels S5 and S6. The well-defined polycrystalline taenite is indicative of petrologic types 4 and 5 due to the conserved internal tetrataenite rim at the boundaries. The presence of polycrystalline taenites and the characteristics of the Agrell Effect suggest that the Santa Filomena meteorite did not reheat above 700°C. The absence of martensite confirms reheating temperatures <800°C and a slow cooling rate. The Ni contents and sizes of the zoned taenite particles indicate a slow cooling rate ranging from 1 to 10 K Myr−1.